Metode Qiroati dan Implementasinya dalam Pembelajaran Literasi Al-Qur'an di MI Sultan Fatah Demak - Anam, Khairul; Aniq, Muhammad (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2025)
The teaching of Qur’anic literacy at the elementary education level, particularly in Madrasah Ibtidaiyah (MI), serves not only as a foundational pillar of Islamic education but also as a crucial instrument for shaping students’ spiritual, moral, and intellectual development. This study investigates the implementation of the Qiroati method at MI Sultan Fatah Demak, a prominent Islamic institution in Central Java, Indonesia. The Qiroati method emphasizes direct, fluent Qur’anic reading without spelling each letter, and it strictly adheres to the rules of makhraj (pronunciation) and tajwid (recitation). Employing a qualitative research design, data were gathered through observation, in-depth interviews with teachers and school leaders, and document analysis. The method of triangulation was used to ensure data validity. The research reveals that the Qiroati method is implemented through a structured pedagogical model consisting of three phases: habituation (daily group reading of short surahs and prayers), classical instruction (collective guided reading with visual aids), and individual reading sessions (student-led recitation assessed by teachers). These stages reflect a blend of educational theories—behaviorism, constructivism, and audiolingual approaches—which enhance both linguistic and affective aspects of learning. The findings demonstrate that the Qiroati method has significantly improved students’ proficiency in reading the Qur’an, not only in technical fluency but also in fostering religious discipline and ethical character. Supporting factors include qualified instructors certified through syahadah training, school policy alignment, structured class systems, and active parental involvement. However, the research also identifies challenges such as students’ lack of motivation, limited family support at home, and tardiness that disrupts learning routines. To address these, the school implements personalized mentoring, strengthens school-family collaboration, and utilizes engaging teaching media. This study contributes to the discourse on Qur’anic pedagogy by positioning the Qiroati method as a holistic model for Qur’anic literacy that integrates educational theory with spiritual formation. It offers actionable insights for Islamic schools seeking to enrich their Qur’anic education programs through contextual, inclusive, and systematic methods